Testing of Drinking Water Reservoirs Coating - H. Sulaymon, Abbas; A. Merdaw, Ali (Iraqi Journal of Chemical and Petroleum Engineering, 2007)
The present study refers to a ready-made three components epoxy based paint made by the Modern Paints Industries Company (Al-Za'farania, Baghdad) subjected to several tests in order to improve its specifications by optimizing the application conditions. The paint components are under the trade names: Resin (D-5547), Hardener (H-1457) and Thinner (P-851). The paint is used for painting drinking water reservoirs from inside.